Autoimmunity to Sphingosine-1-Phosphate-Receptors in Systemic Sclerosis and Pulmonary Arterial Hypertension - Gluschke, Hans; Siegert, Elise; Minich, Waldemar B.; Hackler, Julian; Riemekasten, Gabriela; Kuebler, Wolfgang M.; Simmons, Szandor; Schomburg, Lutz (Frontiers in Immunology, 2022)
CONTEXT: Pulmonary arterial hypertension (PAH) is a frequent extracutaneous manifestation of systemic sclerosis (SSc). PAH is characterized by increased vasomotor tone, progressive remodeling of pulmonary arteries and arterioles, consequentially increased pulmonary vascular resistance, right heart hypertrophy, and eventually right ventricular failure. Autoimmunity against G-protein coupled receptors (GPCRs) has been implicated in the development of SSc-associated PAH. Sphingosine-1-phosphate (S1P) receptors (S1PR) present a potential, yet so far untested antigen for PAH autoimmunity, given the documented role of S1P/S1PR signaling in PAH pathogenesis. OBJECTIVE: We hypothesized that S1P receptors (S1PR) may constitute autoantigens in human patients, and that the prevalence of autoantibodies (aAb) to S1PR1, S1PR2 and S1PR3 is elevated in SSc patients and associated with PAH. METHODS: For this exploratory study, serum samples from 158 SSc patients, 58 of whom with PAH, along with 333 healthy control subjects were screened for S1PR-aAb. S1PR1-3 were expressed as fusion proteins with luciferase in human embryonic kidney cells and used to establish novel in-vitro assays for detecting and quantifying S1PR-aAb. The fusion proteins were incubated with serum samples, the aAb-S1PR complexes formed were precipitated by protein-A, washed and tested for luciferase activity. Commercial anti-S1PR-antibodies were used to verify specificity of the assays. RESULTS: All three assays showed dose-dependent signal intensities when tested with S1PR-subtype specific commercial antibodies. Natural aAb to each S1PR were detected in healthy controls with a prevalence of <10% each, i.e., 2.7% for S1PR1-aAb, 3.6% for S1PR2-aAb, and 8.3% for S1PR3. The respective prevalence was higher in the cohort of SSc patients without PAH, with 17.1% for S1PR1-aAb, 19.0% for S1PR2-aAb, and 21.5% for S1PR3. In the subgroup of SSc patients with PAH, prevalence of aAb to S1PR2 and S1PR3 was further elevated to 25.9% for S1PR2-aAb, and 27.6% for S1PR3. Notably, the majority of patients with positive S1PR2-aAb (60.7%) or S1PR3-aAb (71.9%) displayed interstitial lung disease. CONCLUSION: S1PR1–3 can constitute autoantigens in humans, particularly in SSC patients with PAH. The potential pathophysiological significance for the etiology of the disease is currently unknown, but the elevated prevalence of S1PR2-aAb and S1PR3-aAb in SSC patients with PAH merits further mechanistic investigations.